Inventory Management of Spare Parts Using ABC Classification Method (Case Study: PT Bina Sarana Sukses) - Mentaruk, Ayup; Sitania, Farida Djumiati; Wahyuda, Wahyuda (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
The increasing coal production directly requires special attention in inventory management. This research aims to categorize spareparts inventory based on ABC classification. PT Bina Sarana Sukses has 20,108 spare parts. The method used is ABC classification, dividing inventory into three categories based on the type of inventory and the amount of capital used. The classification results in three classes A, B, and C. Class A absorbs IDR 9,482,425,725 or 80.5% of the total inventory value, consisting of 26 items (25%). Class B absorbs IDR 1,819,909,151 or 15% of the total inventory value, consisting of 33 items (32%). Class C absorbs IDR 478,231,982 or 4.5% of the total inventory value, consisting of 45 items (43%). Based on the classification results, different control strategies are applied for each spare part class. Class A includes strict supervision, automatic ordering, and procurement priority. Class B includes periodic control and supplier evaluation. Class C includes minimal control and needs evaluation.